Correlation of perfusion index change and analgesic efficacy in transforaminal steroid injection for lumbosacral pain, a prospective observational study - Heley Gatorwala; Ananda Bangera (Saudi Journal of Anaesthesia)
Background and Aims: Low back pain is a common problem and a major burden to society. Transforaminal epidural steroid injection is one of the most effective treatment modalities for back pain. We aim to objectively quantify pain relief of lumbosacral radicular pain post transforaminal steroid injection by correlating perfusion index (PI), reflecting real-time peripheral blood flow change at the site of monitoring, controlled by sympathetic system with Numerical rate score (NRS) and SLRT improvement. Material and Methods: A prospective observational study, conducted at K.S Hegde Medical Academy, Mangaluru, from June 2021 to June 2022 as a time-bound study. After IEC clearance (IEC certificate number) for the procedure and study, patients undergoing transforaminal epidural steroid injection for lumbosacral radicular pain were enrolled, excluding those meeting the exclusion criteria. PI change and NRS score improvement were noted at 0, 5, 10, 15, and 30 minutes along with pre and post-procedure SLRT. Results were analyzed. Results: A total of 40 patients were analyzed. PI change at 30 minutes was 2.113 from a baseline of 0.217. Median NRS of 5, improved to 0 and the mean SLRT of 45.17 to 61.45 at the end of 30 minutes. All changes are statistically significant with P (<0.01). correlation between the PI change with NRS is mild (-0.312). Conclusion: PI change ratio shows an overall improvement in pain levels objectively, in a non-invasive, easy, and reliable way. Simultaneous improvement in both NRS and SLRT is clinically significant but cannot predict a correlated quantitative measure of pain relief.